The The Effect of Brand Activism, Perceived Quality, and Brand Reputation on Customer Loyalty with Customer Satisfaction as a Mediating Variable (International Journal of Economics and Management Research, 2025)
Customers of McDonald's in Banjarmasin will be the subjects of an empirical study that aims to mediate the relationship between brand activism, perceived quality, and brand reputation and customer loyalty via the medium of customer happiness. The study's methodology was quantitative and based on a causal connection design. A total of 153 people met the inclusion criteria of being at least 18 years old and having bought McDonald's items at least three times. This selection was done via purposive sampling. A questionnaire was used to gather data, which was then analyzed using SmartPLS software and Partial Least Squares (PLS). Brand activism, perceived quality, reputation, and customer happiness are the factors that have the most impact on brand loyalty, according to the data. Having said that, consumer pleasure is unaffected by brand reputation. These findings suggest that McDonald’s should prioritize enhancing product quality and customer satisfaction while maintaining a positive brand image through effective brand activism and reputation management.